Pembuatan Dan Pemanfaatan Alat Bantu Berjalan Untuk Lansia Di RT 92 Kelurahan Manggar - Gad Gunawan; Chaerul Qalbi AM; Devy Setiorini Sa’adiyah; Suardi; Rijal Surya Rahmany; Achmad Fahrizul Hasmi; Dhio Stofani; Dimas Rizqi Fahrezi; Febrillian Bima Jagad Saksana; Muhammad Syaiful Umara; Ricko Orientius Paseru (CV. Multi Kreasi Media, 2025)
As an institution equipped with resources and experts in the field of technology, universities hold significant potential to develop and provide innovative solutions to the challenges faced by the elderly. Therefore, this activity aims to design and implement a specialized walking aid tailored specifically for older adults. This assistive device will be developed with careful consideration of the unique needs and limitations commonly experienced by the elderly. The introduction of such a device is expected to promote greater independence and active engagement among elderly individuals in their daily lives. Ultimately, it is anticipated that this will enhance their overall quality of life and generate positive social impacts across the broader community in Kalimantan. Furthermore, this activity emphasizes the importance of collaborative efforts among universities, local governments, healthcare institutions, and the community in supporting and effectively implementing this initiative. The project will begin with consultations involving neighborhood leaders (RT) and local residents. Upon reaching a consensus, the next stages will involve socialization, the design and development process, and the eventual delivery of a prototype that meets the identified needs.